METACOGNIÇÃO E SUAS FERRAMENTAS PARA O APRENDIZADO (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2021)
Considering the relevance of reflective thinking at any educational level, this essay aimed at unveiling considerations about metacognition, and particularly its tools as a resource to support teachers and to student learning. The method adopted included a bibliographical survey whose sources were organized in order to allow the development of a discussion about the general and functional characteristics of metacognition and its relationship with the educational environment. It is concluded that metacognitive thinking promotes educational benefits such as awareness of cognitive processes and the capacity for self-regulation of learning. However, the development of these skills depends in most cases on mediation exercised by the teacher. A form of mediation proposed in this study corresponds to the use of metacognitive teaching strategies (MES) capable of connecting the instruction of scientific contents to the development of metacognitive thinking and the self-regulation of learning.
Keywords: Metacognition; Self-Regulation; Strategies; Teaching; Metacognitive